Clinical Chemistry and Other Laboratory Tests on Mouse Plasma or Serum. Issue 2 (June 2013) - Rathkolb, Birgit; Hans, Wolfgang; Prehn, Cornelia; Fuchs, Helmut; Gailus‐Durner, Valérie; Aigner, Bernhard; Adamski, Jerzy; Wolf, Eckhard; Hrabě de Angelis, Martin
Abstract: Besides hematological analyses, many other parameters, including clinical chemistry and endocrinological values, can be determined from mouse blood samples. For most of these tests, plasma or serum samples are used. Data obtained by these investigations provide indications of genotype effects on metabolism and organ functions. Here we describe in detail the considerations that have to be taken into account to get adequate samples for plasma or serum analyses and the recommended sample processing for different investigations. Furthermore, we describe established methods used in the German Mouse Clinic (GMC) to determine clinical chemical parameters; for more in‐depth analysis of specific classes of biomarkers, we provide instructions for ELISAs (sandwich and competitive) as well as LC‐MS/MS, focusing on markers associated with bone or steroid metabolism in the mouse as working examples. Curr. Protoc. Mouse Biol. 3:69‐100 © 2013 by John Wiley & Sons, Inc.